Differential impacts of rainfall and irrigation on agriculturalproduction in Nigeria: Any lessons for climate-smart agriculture? (2016)
The rain-fed agriculture system is vulnerable to climate change impact. However, such impact may alsovary by aggregate and sub-sectoral levels of agricultural production. The impact of climate change andvariability on agricultural production would engender appropriate policies and practices towards a sus-tainable agricultural production system. We investigated the differential impacts of rainfall and irrigationon agricultural production in Nigeria, and drew lessons for climate-smart agriculture (CSA) in Nigeria.Using time series data that spanned 43 years and econometric analytical technique, we quantified thedifferential impacts of rainfall and irrigation on aggregate production and sub-sectors (all crops, staples,livestock, fisheries and forestry). Irrigation had positive and significant impact on aggregate agriculturalproduction as well as all sub-sectors of agriculture. These findings suggest the need for the minimizationof the impact of climate-induced production risks through CSA which would involve complementarydevelopment of more arable land areas under irrigation in Nigeria. Irrigation would also enhance com-plementary agricultural water management for the development of all the sub-sectors of agriculture,thereby enhancing food security and sustainable agricultural production under prevailing climate changeand variability.